An integrative model as a step toward increasing the awareness of eating disorders in the general population - Vasiliu, Octavian (Frontiers in Psychiatry, 2023)
Eating disorders (EDs) represent a contradictory chapter of clinical psychiatry, i.e., although they are associated with significant prevalence and risks in the long term (including vital risk, especially for anorexia nervosa), the therapeutic resources are minimal and based on low-quality data. Another contradiction arose in the last few decades, i.e., a variety of new EDs have been described, either by clinicians or signaled by mass media, but their systematic exploration is progressing very slowly. Entities like “food addiction,” “orthorexia nervosa,” or “emotional eating disorder” still require intensive exploration in order to find the most accurate diagnostic instruments, diagnosis criteria, prevalence data, vulnerability factors, and therapeutic approaches. This article is focused on integrating into a comprehensive model a variety of EDs not specified or loosely defined by the current international classifications of psychiatric disorders. This framework is intended as an instrument for stimulating clinical and epidemiological research, with potential favorable consequences for therapeutic research. The dimensional model suggested here includes four main categories that accommodate the already recognized EDs (i.e., anorexia nervosa, bulimia nervosa, and binge eating disorder) as well as ten EDs that still need intensive research to find their clinical and pathophysiological characteristics. More good-quality studies are urgently required regarding this topic, based on the mental and physical negative impact these EDs may have in the short and long term, especially in vulnerable populations (e.g., pregnant women, athletes, adolescents, etc.).